Peranan Sistem dan Teknologi Pada Proses Bisnis Organisasi - Al-Faruq, Muhammad Yuda; Nasution, Muhammad Irwan Padli (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study is to determine the role of systems and technology in the organization's business processes. Qualitative research methods are applied to this research by using literature study research, then summarized to obtain data in the study. The result of this research is that information technology plays an important role in the business world, including facilitating communication, information management systems, facilitating CRM, business information sources, improving business operations, integrating business development, increasing business efficiency, information management and increasing profitability and cost efficiency, used to promote or carry out public activities such as news, advertisements, and other knowledge information. Information technology can also help achieve organizational strategies in making relevant and accurate decisions.